Приключения майора Звягина: [роман] / М. Веллер - Веллер Михаил Иосифович (Странник и его страна, 2015)
Экземпляры: аб. (20171122) / Инвентарный номер: 57902 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 27 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4